The Story behind the Correction of Risaleh Qusheirie Translation - M Rozatian (متن شناسی ادب فارسی, 2013)
In fifth century, simultaneous with the flourishing of mystical issues and prevalence of various writings in the field of Islamic mysticism, via his deep understanding of mystical thoughts, Abulqasem Qusheiri created a work which had a high status from the beginning and was translated into Persian shortly after. Ascribed to Abu Ali Othmani, the translation of this work was corrected and published by Forouzanfar for the first time almost fifty years ago. Regarding the preface and annotations of Forouzanfar, this work has many advantages but there are also a number of shortcomings in the text and its annotations and, given time, the need for an authentic text of Risaleh Qushirie translation for teaching in postgraduate courses, necessitates the re-correction of this translation. Recently, a new correction by Mehdi Mohabati has been published which raised a number of questions like: Does this new translation come up to expectations of readers for an authentic text or it still repeats the very shortcomings of the previous correction? This article aims to answer such questions.